S86 Effects of exposure to IL-13, IL-31 and an IL-13/31 combination on mucociliary differentiation of bronchial epithelial cells from normal children. (16th November 2010) - Parker, J C; Thavagnanam, S T; Skibinski, G; Heaney, L G; Shields, M D
Abstract : Background: Asthma is characterised by airway remodelling which includes smooth muscle hypertrophy, goblet cell hyperplasia and subsequent mucus hyper-secretion. Th2 cytokines including IL-13 and more recently IL-31 have been implicated in the pathogenesis of asthma. Objectives: We aimed to examine the effects of IL-13 (20 ng/ml), IL-31 (20 ng/ml) and an IL-13/31 combination (20 ng/ml of both) on the in vitro mucociliary differentiation of paediatric bronchial epithelial cells (PBECs) from normal patients. Hypothesis: We hypothesised that cells from normal children exposed to IL-13, IL-31 or an IL-13/31 combination would alter their phenotype towards that of an asthmatic epithelium. Methods: Markers of differentiation, real time PCR for MUC5AC, MUC5AC ELISA and transepithelial electrical resistance (TEER) were assessed. Results: We found that well-differentiated paediatric bronchial epithelial cells highly expressed the IL-31 receptor (IL-31RA). Transepithelial electrical resistance (TEER) indicated good formation of tight junctions which was found to be similar across all treatment groups. We found that IL-13 stimulation reduced the number of ciliated cells compared with control (IL-13 stimulation: mean=4.8% (SD=2.5); Control: mean=18.1%, (SD=5.9)). We did not find that the combination of IL-13 and IL-31 had any additional effects to that of IL-13 alone (IL-13/31 combination stimulation: mean=5.1% (SD=4.6); Control: mean=18.1%, (SD=5.9)). Stimulation with IL-13, IL-31 and the IL-13/IL-31 combination did not result in any changes of goblet cell numbers. Conclusions: IL-31RA receptor is present in abundance in well-differentiated paediatric bronchial epithelial cells however IL-31 does not exhibit any detrimental effects on mucociliary differentiation or proliferation. In addition, IL-31 does not appear to have a synergistic effect when combined in culture with IL-13, in the differentiation process.